The Dialectic of Natural Law and Fiqh Al-Mu'amalah in Determining Copyright as A Fair Marital Property - Lily Andayani; Nandang Sambas (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Copyright has increasingly become an economically valuable intangible asset, yet its legal status as marital property remains uncertain within Indonesia's pluralistic legal system. This study examines how the dialectical interaction between Western Natural Law and fiqh al-mu'amalah can establish a coherent normative framework for determining copyright as fair marital property. Employing normative legal research, the study applies statutory, conceptual, comparative, philosophical, and Islamic legal approaches to analyze primary, secondary, and tertiary legal materials through doctrinal interpretation and dialectical synthesis. The findings reveal that both legal traditions converge in recognizing copyright as an intangible property rissght while distinguishing between its moral and economic dimensions. Moral rights remain exclusively attached to the creator, whereas economic rights and royalties acquired during marriage may constitute marital property subject to equitable distribution based on each spouse's contribution. The study proposes an integrated normative framework grounded in distributive justice, maqashid al-shari'ah, hifzh al-mal, and maslahah to address existing legal uncertainty and strengthen coherence between intellectual property law and family law. By bridging Western legal philosophy and Islamic jurisprudence, this research contributes a theoretically grounded and practically applicable framework that supports judges, legislators, and legal practitioners in resolving copyright-related marital property disputes more consistently and equitably.